Fat- and fiber-related diet behavior among type 2 diabetes patients from distinct regions - Hendrychova, Tereza; Vytrisalova, Magda; Alwarafi, Abdullah; Duintjer Tebbens, Jurjen; Vankatova, Helena; Leal, Sandra; Kubena, Ales Antonin; Smahelova, Alena; Vlcek, Jiri (Patient preference and adherence, 2015)
PURPOSE: Diet and eating habits are of key importance in patients with type 2 diabetes mellitus (T2DM). The purpose of this comparative study was to analyze fat- and fiber-related behavior (FFB) in patients with T2DM from distinct cultural areas. PATIENTS AND METHODS: Observational study was carried out in the Czech Republic (CR) (n=200), the US (n=207), and Yemen (n=200). Patients completed the Fat- and Fiber-related Diet Behavior Questionnaire (FFBQ). RESULTS: Differences in all aspects of FFB among countries were found (P<0.05). The best fat-related behavior reported was from patients from the CR. Patients from the US showed the worst fat-related behavior in total. On the other hand, patients from the US reported the best fiber-related behavior. Patients from Yemen reached the worst scores in all fat-related domains. Patients from all studied countries reported the best results in the "modify meat" and "avoid fat as flavoring" and the worst in the "substitute high fiber" subscales. CONCLUSION: Professionals involved in the diet education of T2DM patients should be aware of the specificity of diet in their country when advising patients keeping general recommendations. We suggest them to be as specific as possible and concentrate on fiber-related behavior.
Keywords: fiber-related behavior; geographical difference; fat-related behavior; Fat- and Fiber-related Diet Behavior Questionnaire; type 2 diabetes mellitus